The toxic effects of cadmium on cell division and chromosomal morphology of Hordeum vulgare - Zhang, Yixian; Yang, Xiaolan (Mutation Research, 1994)
The effects of cadmium at different concentrations (0.5–20 ppm) on root growth, cell division and chromosomal morphology of Hordeum vulgare were studied. The rate of root growth and mitotic index decreased progressively with increasing cadmium concentration and treatment duration. Different concentrations of cadmium could cause mitotic irregularities comprising c-mitoses, anaphase bridges, breaks, stickiness, lagging and vagrant chromosomes and micronuclei. The intensity of the toxic effects is basically dependent on the cadmium concentration and duration of treatment.